Knowledge, attitude, and practice regarding tuberculosis in a labor-intensive industrial district - Jin Li; Liping Lu; Jinyan Zou; Yong Li; Lijuan Fu; Qi Zhao (Frontiers Media S.A., 2024)
BackgroundIn China, tuberculosis (TB) is a major contributor to deaths caused by infectious diseases, with a significant number of cases remaining undetected. Lack of knowledge could heighten the chances of infecting TB. Due to the lack of information on the knowledge, attitudes, and practices (KAP) related to TB among labor-intensive businesses, the study aimed to evaluate the TB KAP within this demographic.MethodsA descriptive cross-sectional survey was conducted among 1,007 participants from March 1 to 28, 2023. A survey was created for assessing knowledge, attitudes, and practices related to tuberculosis, and was sent to employees within the company. We utilize t-tests, ANOVA, and multiple linear regression to investigate the relationship between TB knowledge, attitudes, and practices and various influencing factors.ResultsThe mean good scores rate for TB KAP were 43.5, 23.5, and 75.3%, respectively. Native, female, and workers living in their own houses had a higher score in TB knowledge. Native, non-operators, and workers with a history of TB contact had higher scores in TB practice. Regarding the multivariable linear regression analysis, sex, seniority, birthplace, marital status, and sources of information were associated with greater knowledge; monthly income categories were associated with greater attitude; and position, birthplace, and contact history were associated with greater practice.ConclusionThe survey results lead to the assumption that the level of KAP toward TB is not high among manufacturing workers in Songjiang district. Therefore, it is crucial to enhance tuberculosis knowledge, attitudes, and practices within this demographic.